PENGARUH JUMLAH OBJEK WISATA, HOTEL, DAN RESTORAN TERHADAP PENERIMAAN RETRIBUSI DAERAH DI PROVINSI JAMBI - Ahmad Soleh (Universitas Muhammadiyah Jambi, 2018)
The purpose of this research is to know and analyze the influence of number of tourist object, number of hotel, and number of restaurant to acceptance of regional retribution in Jambi Province. This study uses quantitative methods using secondary data obtained from the Central Bureau of Statistics (BPS) and related agencies. Population in this research is all districts / cities in Jambi Province. The number of samples in this study as many as eleven areas for seven years. Sampling method used purposive sampling technique. The analysis tools used include normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, coefficient determination test R2, and t test. Based on the results of data analysis can be concluded that the variable number of tourist objects affect the acceptance of user charges, the variable number of hotels affect the acceptance of local retribution, and variable number of restaurants affect the acceptance of user charges.